2014
DOI: 10.1111/1462-2920.12444
|View full text |Cite
|
Sign up to set email alerts
|

The genome of Syntrophorhabdus aromaticivorans strain UI provides new insights for syntrophic aromatic compound metabolism and electron flow

Abstract: How aromatic compounds are degraded in various anaerobic ecosystems (e.g. groundwater, sediments, soils and wastewater) is currently poorly understood. Under methanogenic conditions (i.e. groundwater and wastewater treatment), syntrophic metabolizers are known to play an important role. This study explored the draft genome of Syntrophorhabdus aromaticivorans strain UI and identified the first syntrophic phenol-degrading phenylphosphate synthase (PpsAB) and phenylphosphate carboxylase (PpcABCD) and syntrophic t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
64
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 76 publications
(67 citation statements)
references
References 68 publications
2
64
0
Order By: Relevance
“…These Pelotomaculum indeed encode and express genes for syntrophic energy conservation (Hdr-Ifo and ECHyd) and a previously observed pathway for TA degradation to acetate, CO 2 and H 2 (Figure 2 and Supplementary Table S4) (McInerney et al, 2007;Lykidis et al, 2011). In addition, we newly identify expression of a clostridial electron-bifurcating butyryl-CoA dehydrogenase in TAPelo3 that may facilitate the previously hypothesized Sporotomaculum-like energy-conserving butyrate generation from aromatic compound degradation (Qiu et al, 2003;Buckel and Thauer, 2013;Wu et al, 2013;Nobu et al, 2014), albeit refuting the involvement of previously identified non-energy-conserving acylCoA dehydrogenase (Lykidis et al, 2011;Wu et al, 2013). Although butyrate-fermenting TA degradation is thermodynamically more favorable, it sacrifices precious adenosine triphosphate from substrate-level phosphorylation.…”
Section: Metatranscriptomicssupporting
confidence: 55%
See 3 more Smart Citations
“…These Pelotomaculum indeed encode and express genes for syntrophic energy conservation (Hdr-Ifo and ECHyd) and a previously observed pathway for TA degradation to acetate, CO 2 and H 2 (Figure 2 and Supplementary Table S4) (McInerney et al, 2007;Lykidis et al, 2011). In addition, we newly identify expression of a clostridial electron-bifurcating butyryl-CoA dehydrogenase in TAPelo3 that may facilitate the previously hypothesized Sporotomaculum-like energy-conserving butyrate generation from aromatic compound degradation (Qiu et al, 2003;Buckel and Thauer, 2013;Wu et al, 2013;Nobu et al, 2014), albeit refuting the involvement of previously identified non-energy-conserving acylCoA dehydrogenase (Lykidis et al, 2011;Wu et al, 2013). Although butyrate-fermenting TA degradation is thermodynamically more favorable, it sacrifices precious adenosine triphosphate from substrate-level phosphorylation.…”
Section: Metatranscriptomicssupporting
confidence: 55%
“…Although its genome lacks the benzoate degradation pathway, we identify expression of Hdr-Ifo, ECHyd and FixABCX (Figures 2 and 3 and Supplementary Table S2), suggesting the capacity to syntrophically degrade carboxylates. In agreement, this organism expresses a butyrate degradation pathway similar to Syntrophomonas that also depends on identical energy conservation pathways (Supplementary Table S7; Sieber et al, 2010;Nobu et al, 2014). In addition, this clade expresses newly postulated syntrophic branched-chain fatty acid (that is, 2-methylbutyrate, isovalerate and isobutyrate) degradation pathways that are consistent with previous cultivation-based studies (Conrad et al, 1974;Stieb and Schink 1986;Matthies and Schink, 1992) and share high homology with other organisms thought to degrade branched-chain fatty acids (Supplementary Note, Supplementary Figure S5 and Supplementary Table S7).…”
Section: Metatranscriptomicsmentioning
confidence: 62%
See 2 more Smart Citations
“…In addition to the BMC, OP9-1 lineages appear to have other Fd-independent NADH sinks, such as NiFe hydrogenase and alcohol/aldehyde dehydrogenase . However, the putative propionate-oxidizing 'Atribacteria' lineages lack these enzymes as well as NADH:Fd oxidoreductases such as Rnf (Sieber et al, 2012;Nobu et al, 2015a) that syntrophic propionate oxidizers typically rely on to circumvent this issue. The only obvious alternative NADH sink encoded by the putative propionate-oxidizing JS1-1 and JS1-2 lineages involves acetyl-CoA reduction to acetaldehyde by BMC-associated PduPL (Figure 4a), suggesting that the BMC has a critical role in propionate catabolism.…”
Section: Resultsmentioning
confidence: 99%